Cost‐Effective Polymethacrylate‐Based Electrospun Fluorescent Fibers toward Ammonia Sensing. Issue 8 (17th January 2017) - Petropoulou, Afroditi; Christodoulou, Kyriakos; Polydorou, Christiana; Krasia‐Christoforou, Theodora; Riziotis, Christos
Abstract : Polymethacrylate‐based electrospun fluorescent fibrous mats are fabricated upon blending poly(9‐anthrylmethyl methacrylate) (PAnMMA) with the commercially available poly(methyl methacrylate) (PMMA). The PAnMMA/PMMA blended fibers exhibit strong fluorescence (blue emission) thus enabling their evaluation toward ammonia detection. The presented results show a fast response to ammonia even at high concentrations demonstrating the potential applicability of these materials in cost‐effective industrial gas monitoring. Abstract : The fabrication of cost‐effective, polymer‐based electrospun fluorescent fibrous grids and their evaluation as candidates for sensing is reported, drawing useful results on their applicability and efficiency in gas sensing applications. A well‐defined, methacrylic homopolymer functionalized with anthracene moieties as fluorescent elements has been blended with a commercially available poly(methyl methacrylate) for the production of fluorescent electrospun polymer fibers. The formation of 3D grids can provide large interaction area with gas analytes and thus overcome quenching limitations induced by polymeric films, for more efficient sensing. These materials have been evaluated for ammonia sensing based on the fluorescence quenching of the anthracene fluorophores in the presence of ammonia vapors, exhibiting fast response at concentration up to 10 000 ppm. The covalent bonding of the anthracene fluorophore onto a hydrophobic polymethacrylate‐based backbone enables the future exploitation of the presented materials in sensing applications involving metal ions and biomolecules in aqueous media.